Multiparametric flow cytometry analysis of peripheral blood B cell trafficking differences among Epstein-Barr virus infected and uninfected subpopulations - Zachova, Katerina; Kosztyu, Petr; Zadrazil, Josef; Matousovic, Karel; Vondrak, Karel; Hubacek, Petr; Kostovcikova, Klara; Tlaskalova Hogenova, Helena; Mestecky, Jiri; Raska, Milan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2020)
AIMS: Epstein-Barr virus (EBV) targets predominantly B cells and these cells could acquire new phenotype characteristics. Here we analyzed whether EBV-infected and -uninfected B cells from healthy subjects differ in proportion of dominant phenotypes, maturation stage, and homing receptors expression. METHODS: EBV-infected and -uninfected cells were identified by flow cytometry using fluorophore-labeled EBV RNA-specific DNA probes combined with fluorophore-labeled antibody to surface lineage markers, integrins, chemokine receptors, and immunoglobulin isotypes, including intracellular ones. RESULTS: Our results show that the trafficking characteristics of EBERpos B cells are distinct from EBERneg B cells with most dominant differences detected for α4β1 and α4β7 and CCR5 and CCR7. EBV-positive cells are predominantly memory IgM+ B cells or plasmablasts/plasma cells (PB/PC) positive for IgA or less for IgM. In comparison to uninfected B cells, less EBV-positive B cells express α4β7 and almost no cells express α4β1. EBV-positive B cells contained significantly higher proportion of CCR5+ and CCR7+ cells in comparison to EBV-negative cells. In vitro exposure of blood mononuclear cells to pro-inflammatory cytokine IL-6 reduces population of EBV-positive B cell. CONCLUSION: Although EBV-infected B cells represent only a minor subpopulation, their atypical functions could contribute in predisposed person to development abnormities such as some autoimmune diseases or tumors. Using multi-parameter flow cytometry we characterized differences in migration of EBV-positive and -negative B cells of various maturation stage and isotype of produced antibodies particularly different targeting to mucosal tissues of gastrointestinal and respiratory tracts.
Keywords: IgA; cell trafficking; krev; Epstein-Barr virus; Humans; Healthy Volunteers; plasma cell; lidé středního věku; IgM; Female; vezikulární transportní proteiny; Aged; dospělí; senioři; lidé; B-lymfocyty; infekce virem Epsteina-Barrové; Epstein-Barr Virus Infections; Adult; ženské pohlaví; Male; Flow Cytometry; Middle Aged; B-Lymphocytes; Aged, 80 and over; plasma blast; Blood; senioři nad 80 let; průtoková cytometrie; memory B cells; zdraví dobrovolníci pro lékařské studie; naïve B cells; mužské pohlaví; Vesicular Transport Proteins